GENDER CONSTRUCTION IN NUSANTARA FOLKLORE JANUARY EDITION - SUGIARTI (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of this current study is to describe (1) the construction of gender stereotyping in the characters of Nusantara folklore and (2) the gender relation of characters in Nusantara folklore. Sociological literary approach is employed because it seeks to find male and female relation reflected in the text through social dimensions. Qualitative approach is also used to obtain findings through analysis and description of the phenomena, as well as through exploration of contextual meaning. Through descriptive method, this study aims to disseminate gender construction issues reflected in literary works, specifically Nusantara folklore. The research uses data in the form of quotations of narration sequences which reflect gender relation. The primary source of data is a collection of Nusantara folklore published by Adicita Karya Nusa, 2 September 2015 Edition on January. The data collection employs documentation study conducted through critical and creative reading. The data analysis technique is conducted in two ways (a) understanding the meaning of the text thoroughly and (b) extracting morals of the story. The findings have revealed that (1) the construction of gender labeling in the characters manifests into stereotypes against male and female within the story, in which female characters tend to be represented as weak, and (2) the gender relation is reflected through the leadership of female character with dominant feminine traits, as opposed to male leadership, in which due to traditionally associated with power, his actions contradicts his defined characteristics. This current study is expected to (a) contribute to the enrichment of feminism study in literature, (b) expand the application of gender relation theory in literary works, and (c) develop critical thinking on gender construction in literary studies from the perspective of culture. This current study seeks to gradually reconstruct gender labeling in order to maintain human being dignity, and also to adapt with changes in dimension relation for a better civilization.